Incidence of teachers' creative intelligence in their pedagogical practice during the pandemic - Tunjo-Guerrero, Leidy Carolina (2021)
This article shows the incidence of the creative intelligence of teachers in their pedagogical practice, based on the study of 8 cases, in different educational sectors of basic and secondary education in the city of Bogotá-Colombia. The research process used a qualitative approach corresponding to the phenomenology method, with a design centered on case studies. This produced the effectiveness of the research, being verifiable the influence of creativity within the subcategories "knowing how to do", "knowing how to be" and "knowing how to know" of the pedagogical practice developed during the pandemic of 2020. It is concluded that the process of the pedagogical practice applied during the extreme situation of the year 2020, needed flexible and innovative characteristics on the part of the teacher, which solved the different needs of the knowledge of the praxis.